Use of a rapid, efficient inoculation method to induce papillomas by cottontail rabbit papillomavirus DNA shows that the E7 gene is required. - Brandsma, J L (1991)
A simple inoculation method to induce papillomas efficiently with cottontail rabbit papillomavirus (CRPV) DNA is described. Using a jet injector, recombinant CRPV DNA is easily delivered to 100 or more sites per rabbit and induces typical epithelial papillomas in approximately 50% of those sites. Papillomas begin to form by 3 weeks and continue to develop for up to 7 weeks, a pattern similar to that reported following infection with intact virus. This system readily lends itself to investigation of viral gene function by delivering mutant viral genomes into an immunologically intact host. Two mutations in the E7 open reading frame were introduced into the complete CRPV genome and analyzed by this method. One was a frameshift mutation encoding just nine amino-terminal amino acids of the E7 protein; the other was an in-frame insertion mutation at position 9. Both E7 mutations were in a region of homology to the 300-kDa protein binding domain of adenovirus E1A protein. Neither mutant construct was able to induce papillomas, thereby demonstrating that the E7 gene participates in this biologic function. Exploitation of this approach, which demonstrates that a papillomavirus E7 gene is involved in the induction of papillomas in vivo, should permit detailed studies into molecular mechanisms involved in papilloma induction, malignant conversion, and host immune response. The high efficiency of papilloma induction with recombinant CRPV DNA suggests that the jet injector can also be used to study the biologic effects of other genetic elements in rabbits or in other species.